(untitled) (Bangladesh Journal of Bioethics, 2016)
This paper reflects on the question, Is there a sound justification for the existential view that humans have a higher moral status than other animals? It argues that the existential view that humans have a higher moral status than animals is founded on a weak and inconclusive foundation. While acknowledging various arguments raised for a common foundation between human and non-human animals, the paper attempts to establish a common ground for moral considerability of human and non-human animals. The first common foundation is based on the existential notion of being in the world, which is common for both human and non-human animals. The second idea is based on the common desire to actualize different needs. The paper demonstrates these common foundations by referring to Heidegger and Abraham Maslows hierarchy of needs.